KORELASI ANTARA ISLAM DAN EKONOMI - Abidin, Akmal Zainal (Jurnal Penelitian, 2015)
CORELATION BETWEEN ISLAM AND ECONOMY. This paper aims to identifies about the correlation between economic and Islam. Islam is the perfect religion that governs all things in life, including the economy. This is evident with the concept of  well-being which is described in the al-Quran and Sunnah. Basically the goal of every human life is to prosper, although humans make sense of  well- being with a different perspective. Most understand economics assume that welfare is the welfare of  earthly material. But to make sense of well-being with the term al-Falah, is meaning holistic wellbeing and balance between material and spiritual dimensions. al-Quran and Sunnah have taught that the human being will be achieved if  living in balance between material and spiritual. This is because human life does not just stop in the life of this world, but there is still a second life that will be faced by humanity in the hereafter, and well-being will be achieved with the truth is that people can balance the needs of the world and the hereafter, and that is what is taught in Islamic economics.Keywords: Islam, Economy, Prosperity.Tulisan ini bertujuan untuk menjelasakn tentang korelasi antara ekonomi  dan  Islam.  Islam  adalah  agama  yang  sempurna  yang mengatur segala hal dalam kehidupan ini, termasuk juga ekonomi. Hal ini terbukti dengan konsep kesejahteraan yang dipaparkan dalam al-Quran dan Sunnah. Pada dasarnya tujuan hidup setiap manusia adalah untuk mencapai kesejahteraan, meskipun manusia memaknai kesejahteraan dengan perspektif  yang berbeda-beda. Sebagian besar paham ekonomi menganggap bahwa kesejahteraan adalah kesejahteraan material duniawi. Namun Islam memaknai kesejahteraan dengan istilah  Falah  yang  berarti  kesejahteraan  holistik  dan  seimbang antara dimensi material dan spiritual. Al-Quran dan Sunnah telah mengajarkan bahwa kesejahteraan akan tercapai jika manusia menjalani hidup secara seimbang antara material dan spiritualnya. Ini karena kehidupan manusia tidak hanya berhenti di dalam kehidupan dunia saja, namun masih ada kehidupan kedua yang akan dihadapi manusia di akhirat kelak, dan kesejahteraan akan tercapai dengan sesunguhnya jika manusia dapat menyeimbangkan keperluan dunia dan akhirat, dan itulah yang diajarkan dalam ekonomi Islam.Kata Kunci: Islam, Ekonomi, Kesejahteraan.